Vismodegib or cixutumumab in combination with standard chemotherapy for patients with extensive‐stage small cell lung cancer: A trial of the ECOG‐ACRIN Cancer Research Group (E1508). Issue 15 (10th May 2016) - Belani, Chandra P.; Dahlberg, Suzanne E.; Rudin, Charles M.; Fleisher, Martin; Chen, Helen X.; Takebe, Naoko; Velasco, Mario R.; Tester, William J.; Sturtz, Keren; Hann, Christine L.; Shanks, James C.; Monga, Manish; et al.
Abstract : BACKGROUND: Preclinical targeting of the hedgehog pathway by vismodegib and of insulin‐like growth factor 1 receptor by cixutumumab enhances the efficacy of chemotherapy and also demonstrates activity against the tumor cell fraction responsible for disease recurrence in small cell lung cancer. METHODS: Patients with newly diagnosed extensive‐stage small cell lung cancer (SCLC‐ED) were randomized to receive four 21‐day cycles of cisplatin and etoposide alone (cisplatin at 75 mg/m 2 on day 1 and etoposide at 100 mg/m 2 on days 1‐3; arm A) or in combination with either vismodegib (150 mg/d by mouth; arm B) or cixutumumab (6 mg/kg/wk intravenously on day 1; arm C). The primary endpoint was progression‐free survival (PFS). Circulating tumor cells (CTCs) were isolated/enumerated with the Veridex CellSearch platform at the baseline. RESULTS: One hundred fifty‐two eligible patients were treated. Patient demographics and disease characteristics were well balanced between the 3 arms except for the higher rate with a performance status of 0 in arm B ( P = .03). The median PFS times in arms A, B, and C were 4.4, 4.4, and 4.6 months, respectively; the median overall survival (OS) times were 8.8, 9.8, and 10.1 months, respectively; and the response rates were 48%, 56%, and 50%, respectively. None of the comparisons of these outcomes were statistically significant. The median OS was 10.5 months for those with low CTC counts (≤100/7.5 mL) at baseline and 7.2 months for those with high CTC counts (hazard ratio, 1.74; P = .006). CONCLUSIONS: There was no significant improvement in PFS or OS with the addition of either vismodegib or cixutumumab to chemotherapy in patients with SCLC‐ED. A low baseline CTC count was associated with a favorable prognosis. Cancer 2016;122:2371–2378 . © 2016 American Cancer Society . Abstract : The addition of vismodegib or cixutumumab to cisplatin and etoposide for patients with extensive‐stage small cell lung cancer does not demonstrate an overall benefit. A low baseline circulating tumor cell count is associated with an overall favorable prognosis for patients with extensive‐stage small cell lung cancer.